2017
DOI: 10.4038/sljch.v46i3.8322
|View full text |Cite
|
Sign up to set email alerts
|

The association of the hydration status and parental knowledge on fluid consumption with children’s weight status in Malaysia

Abstract: Introduction: Hydration and obesity play an important role in body weight regulation.Objective: To determine the association of hydration status and parental knowledge on fluid intake with the children's weight status in Muar, Johor, Malaysia.Method: A total of 207 children, 7-13 years of age, and their parents participated in this crosssectional study. Parental fluid consumption knowledge questionnaire and beverage questionnaire were used to assess parent's knowledge on fluid consumption and children's fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…The results show that less than one-third (29.6%) of the adolescents in this study meet the RNI of 2,000-2,200 mL of fluid daily [21], and that result is similar to those in previous studies [15]. The adolescents' mean total daily fluid intake in the current study was much lower than those in Indonesia [22] and Latin America [23] but higher than that in European adolescents [24] Those results were consistent with the hydration status results for the adolescents, which showed that more than half (67.0%) of the adolescents were inadequately hydrated which was similar to the results of a study in Egypt [25] and much higher than that reported in a study in the United States [4].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results show that less than one-third (29.6%) of the adolescents in this study meet the RNI of 2,000-2,200 mL of fluid daily [21], and that result is similar to those in previous studies [15]. The adolescents' mean total daily fluid intake in the current study was much lower than those in Indonesia [22] and Latin America [23] but higher than that in European adolescents [24] Those results were consistent with the hydration status results for the adolescents, which showed that more than half (67.0%) of the adolescents were inadequately hydrated which was similar to the results of a study in Egypt [25] and much higher than that reported in a study in the United States [4].…”
Section: Discussionsupporting
confidence: 89%
“…The pattern of beverage consumption observed in this study was similar to those in past studies in which plain water was the main source of fluid [15,26]. In this study, water intake was followed by that for malted drinks, a fluid source that is prevalent among Malaysian children [17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation